Interactions between gut microbiota and Parkinson's disease: The role of microbiota-derived amino acid metabolism - Wang, Wang; Jiang, Shujun; Xu, Chengcheng; Tang, Lili; Liang, Yan; Zhao, Yang; Zhu, Guoxue (Frontiers in Aging Neuroscience, 2022)
Non-motor symptoms (NMS) of Parkinson’s disease (PD), such as constipation, sleep disorders and olfactory deficits, may emerge up to 20 years earlier than motor symptoms. A series of evidence indicate that the pathology of PD might derived from the gastrointestinal tract. Numerous studies support that the gut microbiota communicate with brain through immune system, special amino acid metabolism, nervous system in PD. Recently, there is growing recognition that the gut microbiota play a vital role in the modulation of multiple neurochemical pathways via “gut microbiota-brain axis” (GMBA). Many of gut microbiota metabolites, such as fatty acid, amino acids, and bile acid, convey signaling functions as they mediate the crosstalk between gut microbiota and host physiology. Amino acids abundance and species alteration including glutamate, trytophan may disturb the signaling transmission between nerve cells and disrupt the normal basal ganglia function in PD. Specific amino acids and their receptors are considered as new potential targets for ameliorating PD. The present study aimed to systematically summarize all available evidence on the gut microbiota-derived amino acid metabolism alterations associated with PD.